Reducing the Risk of Groundwater Contamination by Improving Fertilizer Storage & Handling - Hickman, John S.; Herbel, Kevin L.; Rogers, Danny H.; Powell, Morgan (My University, 1998)
Assists with ranking farmstead soils and geologic conditions by their ability to keep contaminants out of groundwater.
EP35_1998-08
Keywords: EP35; Environment and Natural Resources; Health and Safety; EP